Memanfaatkan Materi Balok Alami untuk Meningkatkan Kemampuan Motorik Halus di Pendidikan Anak Usia Dini (PAUD) AL-IBRA di Desa Persiapan Waesuhan, Kabupaten Buru - Tutupary, Rosmaryn; Kundre, Junita L. (Balitbangda Provinsi Lampung, 2018)
Early Childhood Education (PAUD) aims to accommodate the development of children in all aspects, including physical, intellectual, socio-emotional, language, and communication, in accordance with their developmental stages. The use of various learning media plays a significant role in achieving this goal, helping to clarify the messages conveyed and requiring teachers' creativity in selecting media that meet children's needs. One effective option is to use natural materials such as stones, wood, and leaves, which are not only economical but also easily accessible, thus supporting effective and efficient learning. The utilization of natural media by teachers can also complement cognitive, socio-emotional, motor, moral, and religious values aspects in children. The purpose of this study is to evaluate the effectiveness of using natural materials media in developing fine motor skills in children aged 5-6 years at PAUD Al-Ibra, Persiapan Waesuhan Village, Lolong Guba District, Buru Regency, using the Classroom Action Research (CAR) method focused on the classroom context. The research subjects consist of 10 early childhood children, with a breakdown of 4 boys and 6 girls. The research process is conducted in two cycles covering planning, implementation, observation, and reflection stages. It is hoped that the results of this study will provide a better understanding of the effectiveness of using natural materials media in developing fine motor skills in early childhood.